Assessment of subcutaneous adipose tissue using ultrasound in highly trained junior rowers - Kelso, A.; Trajer, E.; Machus, K.; Treff, G.; Müller, W.; Steinacker, J. M. (European Journal of Sport Science, 2017)
There is a large variety of body fat (BF) measurements, which differ in validity and reliability. The aim of this study was to measure subcutaneous adipose tissue (SAT) using ultrasound (US) in highly trained junior rowers in a field setting, establish fat patterning profiles, and compare the profiles between male and female athletes. Skinfold thickness (SKF) measurements were also taken and compared to US measurements. Methods: Sixteen athletes participated. US measurements were taken at eight sites and reported as a sum of SAT (D): DExcl (without embedded structures) and DIncl (including embedded structures). SKF was measured at three sites and reported as a sum of adipose tissue thickness (SUMSKF). Results: Mean SAT thickness (DIncl) was 27.6 ± 12.4 mm for males and 65.5 ± 11.8 mm for females. Females had significantly more embedded structures than males (P = .016). Significant correlations were found (P < .001, r = 0.92) comparing SUMSKF to DIncl and between SKF and US measurements at the thigh site (P < .001, r = 0.86). Conclusion: US is a suitable tool to measure BF in the field testing of athletes and enables measurements of SAT with an accuracy and reliability not reached before. The sum of thicknesses (DIncl or DExcl) can be used to represent subcutaneous fat based on accurate measurements of uncompressed SAT thicknesses.